KOHESI GRAMATIKAL DALAM BERITA KASUS FERDY SAMBO - Mimi Hermita; Afrini Rahmi; Asri Wahyuni Sari (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to describe how grammatical cohesion is used in the news about the Ferdy Sambo case and to reveal the meaning of the news through the use of grammatical cohesion. This research is qualitative and uses the content analysis method. The data used are sentences containing grammatical cohesion in the news of the Ferdy Sambo case from the online news site detik.com. Based on the analysis of data from detik.com between July 2022 and March 2023, it was found that the grammatical cohesion that is often used is reference, substitution, ellipsis, and conjunction. Conjunction is the most widely used type of cohesion, while ellipsis is the least frequent. However, all these types of grammatical cohesion play an important role in maintaining the continuity of the news and helping readers understand what the writer is saying. In addition, these four types of grammatical cohesion help explain the chronology of the shootout that resulted in Brigadier Yoshua's death. The news also explained the role of Ferdy Sambo and the investigating team in uncovering the truth that Ferdy Sambo was the brain behind the murder.